Safety and efficacy of dendritic cell vaccine for COVID-19 prevention after 1-Year follow-up: phase I and II clinical trial final result - Jonny, Jonny; Putranto, Terawan Agus; Yana, Martina Lily; Sitepu, Enda Cindylosa; Irfon, Raoulian; Ramadhani, Bunga Pinandhita; Sofro, Muchlis Achsan Udji; Nency, Yetty Movieta; Lestari, Endang Sri; Triwardhani, Ria; Mujahidah,; Sari, Retty Karisma; et al. (Frontiers in Immunology, 2023)
Introduction Interim analysis of phase I and phase II clinical trials of personalized vaccines made from autologous monocyte-derived dendritic cells (DCs) incubated with S-protein of SARS-CoV-2 show that this vaccine is safe and well tolerated. Our previous report also indicates that this vaccine can induce specific T-cell and B cell responses against SARS-CoV-2. Herein, we report the final analysis after 1 year of follow-up regarding its safety and efficacy in subjects of phase I and phase II clinical trials. Methods Adult subjects (>18 years old) were given autologous DCs derived from peripheral blood monocytes, which were incubated with the S-protein of SARS-CoV-2. The primary outcome is safety in phase I clinical trials. Meanwhile, optimal antigen dosage is determined in phase II clinical trials. Corona Virus Disease 2019 (COVID-19) and Non-COVID-19 adverse events (AEs) were observed for 1 year. Results A total of 28 subjects in the phase I clinical trial were randomly assigned to nine groups based on antigen and Granulocyte-Macrophage Colony Stimulating Factor (GM-CSF) dosage. In the phase II clinical trial, 145 subjects were randomly grouped into three groups based on antigen dosage. During the 1-year follow-up period, 35.71% of subjects in phase I and 16.54% in phase II had non-COVID AEs. No subjects in phase I experienced moderate–severe COVID-19. Meanwhile, 4.31% of subjects in phase II had moderate–severe COVID-19. There is no difference in both COVID and non-COVID-19 AEs between groups. Conclusions After 1 year of follow-up, this vaccine is proven safe and effective for preventing COVID-19. A phase III clinical trial involving more subjects should be conducted to establish its efficacy and see other possible side effects.